Mental Health Literacy among the Palestinian-Arab Minority in Israel and Its Correlates with Mental Health Service Use. (14th March 2023) - Abo-Rass, Fareeda; Abu-Kaf, Sarah
Abstract : Background . Mental health literacy (MHL) has been proposed as a factor in facilitating the utilization of mental health services. This study examined MHL among the Palestinian-Arab minority in Israel, based on Jorm's six-dimension framework, and the contribution of each MHL dimension to mental health service use. Methods . A cross-sectional study consisting of a convenience sample of 214 Palestinian-Arabs ( M age  = 36.40 ± 10.77 years, 68.2% female), who completed measures of MHL, psychological distress, mental health service use, and sociodemographic characteristics. The differences between participants who reported using mental health services (30.38%) and those who did not were examined using t - and χ 2 tests. Binary logistic regression analysis was conducted to identify service use determinants. Results . Participants reported moderate or high levels on all MHL dimensions. Compared to those who did not report mental health service use, those who did had significantly (p < 0.001 ) higher MHL levels on three dimensions: knowledge of professional help available, knowledge of where to seek information, and attitudes that promote recognition or appropriate help-seeking behavior. The regression analysis indicated that the main determinants of mental health service use were psychological distress ( OR  = 1.70, 95% CI: 1.44–2.01), knowledge of where to seek information ( OR  = 1.16, 95% CI: 1.02–1.32), and attitudes that promote recognition or appropriate help-seeking behavior ( OR  = 1.08, 95% CI: 1.02–1.14). Practice implications . This study underlines MHL's crucial role and indicates that it is not only objective characteristics or psychological distress that determine service use among Palestinian-Arabs in Israel. Rather, individuals' knowledge of where to seek information and attitudes promoting recognition or help-seeking behavior are also important determinants. Interventions targeting these two MHL dimensions may help increase mental health service use among this population.